2013
DOI: 10.1038/cmi.2012.74
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell-based immunotherapy for colon cancer using an HLA-A*0201-restricted cytotoxic T-lymphocyte epitope from tumor-associated antigen 90K

Abstract: Tumor-associated antigen 90K is implicated in cell-cell and cell-extracellular matrix adhesion through its interaction with galectin-3 and integrin-b1 and is highly expressed in malignant tissues, making it a novel target for the development of new immunotherapies. We investigated a potential immunotherapy treatment for colon cancer using 90K-specific cytotoxic T lymphocytes induced by autologous dendritic cells and pulsed with 90K peptides. We selected three peptides (90K 351 , 90K 5 and 90K 523 ) that bind t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Previously conducted studies have suggested many tumor-associated antigens (TAA) such as 90 K [35] , 4D10 [36] and GTF2B [23] may serve as targets for colon cancer therapy [37] . Moreover, the relationship between GTF2B, lncRNA LINC00355 and ITGA2 was verified in our study, which showed that overexpression of lncRNA LINC00355 was conducive to promoting the binding of GTF2B to ITGA2.…”
Section: Discussionmentioning
confidence: 99%
“…Previously conducted studies have suggested many tumor-associated antigens (TAA) such as 90 K [35] , 4D10 [36] and GTF2B [23] may serve as targets for colon cancer therapy [37] . Moreover, the relationship between GTF2B, lncRNA LINC00355 and ITGA2 was verified in our study, which showed that overexpression of lncRNA LINC00355 was conducive to promoting the binding of GTF2B to ITGA2.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies ( 7 9 ) have shown that enhancing patients’ antitumor immunity is the best approach to prevent and control tumor metastasis. Cancer immunotherapeutic approaches, such as cancer vaccines ( 10 , 11 ), checkpoint blockade therapies ( 12 , 13 ), and cell-based therapies [such as dendritic cell (DC)–based T cell adoptive transfer] ( 14 16 ), have shown promise. Thus, introducing immunotherapeutic strategies with DDS appears to be a feasible approach to counter metastasis and tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…LGALS3BP encodes the galectin-3-binding protein (Gal-3BP), which was originally reported by several groups in attempts to search for proteins secreted by cancer cells (9, 10). Extending from its discovery, the role of Gal-3BP has been widely studied in the field of cancer research (1119). Since Gal-3BP has a scavenger receptor cysteine-rich (SRCR) domain, which is found in innate immunity-related proteins, the role of Gal-3BP has also been extensively studied in relation to immune reactions (20, 21).…”
Section: Introductionmentioning
confidence: 99%